Synbiotic Effects of Saccharomycescerevisiae, Mannan Oligosaccharides, and β-Glucan on Innate Immunity, Antioxidant Status, and Disease Resistance of Nile Tilapia, Oreochromis niloticus - Gamal El-Nobi; Mohammed Hassanin; Alshimaa A. Khalil; Alaa Y. Mohammed; Shimaa A. Amer; Metwally M. Montaser; Mohamed E. El-sharnouby (MDPI AG, 2021)
Synbiotic (SYN) additives were assessed as an antibiotic alternative on the effects on the nonspecific immune response and disease resistance of O. niloticus to P. aeruginosa. Healthy fish (n = 120, average initial weight 18 ± 2 g) were allotted randomly into four experimental groups (3 replicates for each); 1) a control group with no additives (CON), 2) basal diet complemented with 0.1 g kg-1 diets of norfloxacin, NFLX, 3) basal diet fortified with 1 mL kg-1 diet of SYN, and 4) basal diet complemented with a mixture of NFLX and SYN, which was carried out for eight weeks. Results showed a significant increase (p < 0.01) in the serum immune parameters (total protein, globulin and albumin, nitric oxide (NO), and lysozyme activity) in the SYN group and the NFLX+SYN group compared with the CON and NFLX groups. The serum glucose, cholesterol, and triglycerides were higher in NFLX and NFLX+SYN groups than the CON and SYN groups. The catalase (CAT), superoxide dismutase, glutathione peroxidase (GPX) activities were significantly augmented in the NFLX+SYN group, followed by the SYN group compared with CON and NFLX groups. The cumulative mortality rate (CMR) of O. niloticus following the P. aeruginosa challenge was decreased in the SYN group compared to other groups. The results emphasize that synbiotic could be used as a norfloxacin alternative to enhance the related immunological parameters, including antioxidant activity and disease resistance against P. aeruginosa infection of O. niloticus.